Adopt 10 key strategies for successful leadership. Issue 5 (August 2017) - Hope, Joan
Abstract : NEW ORLEANS — If you're looking for higher‐level leadership opportunities, showing leadership in your current position can get you noticed. Chemene Crawford, vice president for student services and enrollment management at El Centro College in the Dallas County Community College District; and Ann Johnson, vice president for student success at Lone Star College, Tomball, explained how to lead from any position at a session at the American Association of Community Colleges annual convention.